Plant-derived chimeric antibodies inhibit the invasion of human fibroblasts by Toxoplasma gondii - Lim, Sherene Swee Yin; Chua, Kek Heng; Nolke, Greta; Spiegel, Holger; Goh, Wai Leong; Chow, Sek Chuen; Kee, Boon Pin; Fischer, Rainer; Schillberg, Stefan; Othman, Rofina Yasmin (PeerJ, 2018)
he parasite Toxoplasma gondii causes an opportunistic infection, that is, particularly severe in immunocompromised patients, infants, and neonates. Current antiparasitic drugs are teratogenic and cause hypersensitivity-based toxic side effects especially during prolonged treatment. Furthermore, the recent emergence of drug-resistant toxoplasmosis has reduced the therapeutic impact of such drugs. In an effort to develop recombinant antibodies as a therapeutic alternative, a panel of affinity-matured, T. gondii tachyzoite-specific single-chain variable fragment (scFv) antibodies was selected by phage display and bioinformatic analysis. Further affinity optimization was attempted by introducing point mutations at hotspots within light chain complementarity-determining region 2. This strategy yielded four mutated scFv sequences and a parental scFv that were used to produce five mouse–human chimeric IgGs in Nicotiana benthamiana plants, with yields of 33–72 mg/kg of plant tissue. Immunological analysis confirmed the specific binding of these plant-derived antibodies to T. gondii tachyzoites, and in vitro efficacy was demonstrated by their ability to inhibit the invasion of human fibroblasts and impair parasite infectivity. These novel recombinant antibodies could therefore be suitable for the development of plant-derived immunotherapeutic interventions against toxoplasmosis.